Estimating vulnerability to covariate and idiosyncratic shocks - Isabel Günther; Kenneth Harttgen (Georg-August-Universität Göttingen, Ibero-America Institute for Economic Research (IAI), 2006)
Households in developing countries are frequently hit by severe idiosyncratic and covariate shocks resulting in high consumption volatility. A household's currently observed poverty status might therefore not be a good indicator of the household's general poverty risk, or in other words its vulnerability to poverty. Although several measurements to analyze vulnerability to poverty have recently been proposed, empirical studies are still rare as the data requirements for these measurements are often not met by the surveys that are available for developing countries. In this paper, we propose a simple method to empirically assess the impact of idiosyncratic and covariate shocks on households' vulnerability, which can be used in a wide context as it relies on commonly available living standard measurement surveys. We apply our approach to data from Madagascar and show, that whereas covariate and idiosyncratic shocks have both a substantial impact on rural households' vulnerability, urban households' vulnerability is largely determined by idiosyncratic shocks.
Keywords: I32; D60; 330; Armut; Risiko; Schock; Privater Haushalt; Madagaskar